2014
DOI: 10.1097/inf.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Diagnosis of Pediatric Mycobacterial Lymphadenitis Using Fine Needle Aspiration Biopsy

Abstract: FNAB and Xpert MTB/RIF enable a rapid diagnosis in pediatric mycobacterial lymphadenitis, expediting appropriate treatment and potentially preventing morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Lymph node aspiration biopsy is safe, feasible and associated with good sensitivity and specificity in adolescents. 30 Microbiologic confirmation of abdominal, renal, genitourinary, meningeal and musculoskeletal tuberculosis generally requires more invasive sampling, and yields from culture and molecular testing are lower than for thoracic disease.…”
Section: Figurementioning
confidence: 99%
“…Lymph node aspiration biopsy is safe, feasible and associated with good sensitivity and specificity in adolescents. 30 Microbiologic confirmation of abdominal, renal, genitourinary, meningeal and musculoskeletal tuberculosis generally requires more invasive sampling, and yields from culture and molecular testing are lower than for thoracic disease.…”
Section: Figurementioning
confidence: 99%
“…A total of 100 of 121 archival FNAB specimens were selected from a previous study in approximately the same ratio of 1:3 culture negative: positive. The age ranged from 2.6 months to 15 years with a mean of 3.6 years (standard deviation 3.5) and an equal gender distribution.…”
Section: Resultsmentioning
confidence: 99%
“…The ZN stain is specific but has low sensitivity . Mycobacterial culture has for long been the reference standard but its main limitation is a slow turnaround time of 2 to 6 weeks . Xpert MTB/RIF (Cepheid, Sunnyvale, California), a real‐time polymerase chain reaction assay, has shown remarkable sensitivity and specificity and was recommended by the World Health Organization (WHO) in 2013 as the first line diagnostic procedure for TB lymphadenopathy (LAD) .…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the included studies. Five studies were conducted in Africa [13][14][15][16][17], 1 study in India [18], and 1 in Italy [19]. One study was a cohort study [19] and the remaining 6 were prospective studies [13][14][15][16][17][18].…”
Section: Studies Identifiedmentioning
confidence: 99%
“…Regarding applicability, one study (Bholla, M., 2016) had low concern because patients were assessed in a local hospital and another study (Held, M., 2016) had high concern because only inpatients were evaluated at a tertiary-care center [13,14]. Other studies reported unclear concern due to lack of enough information regarding the clinical setting [15][16][17][18][19]. Regarding the index test and reference standard, the included studies generally had a low risk of bias and low applicability concerns.…”
Section: Quality Assessmentmentioning
confidence: 99%